The spatial concepts of cultural heritage village toward a tourism development; A case study of Kadilangu Demak Indonesia - Suprapti, Atiek; Sardjono, Agung Budi; Indriastjario, Indriastjario; Pandelaki, Edward E. (Journal of Architecture and Urbanism, 2019)
Globalization perspective considers the world as a large market, which requires the resources readiness as capital to be able to participate actively. Local culture is an important capital to create identity and social harmonization in constructing a better quality of life. In the 15th–16th century AD, the Java north coast of Indonesia was known for having several old towns with their important roles in spreading Islam. Centuries later the legend of Walisanga still greatly influences the people’s lives particularly in Demak. The Muslim community is living tradition in this area has become one of the identity of the city. The development in the last decades has shown significant impacts on the tourism sector. This phenomenon showed that there would be conflicts of interests between social-cultural sectors and economic sectors. In this kind of situation, the community must adapt spatial settings to accommodate their needs. The purpose of this article is to find the concept of spatial setting formed by economic, cultural and religious factors in this historical area. The locus is the Muslim settlements in Kadilangu Demak a site of Sunan Kalijaga’s heritage. This study that employed qualitative research methods, the three spatial concepts proposed are: (1) the identity space of local culture is strongly exists (2) the shift in the value of space, which has changed from the glory of the noble family to the common people (3) the space for morality control, which functions as the control of community’s moral. The third concepts are local genius, which is significantly potential for tourism.